In vitro study on the osteoimmunological potential of magnesium implants (WE43MEO) - Sabrin Aydin; Ana Prates Soares; Heilwig Fischer; Raphael Silvan Knecht; Alexander Kopp; Katharina Schmidt-Bleek; Max Heiland; Carsten Rendenbach (BioMedical Engineering OnLine)
Abstract Introduction Bioresorbable implants significantly advance orthopedics and regenerative medicine, offering advantages over permanent implants for bone regeneration. They eliminate the need for secondary surgery and reduce long-term risks associated with permanent implants. Magnesium-based alloys are particularly promising, as their biocompatibility and mechanical properties are similar to bone. However, the degradation of magnesium is associated with physiological challenges that need to be better understood. Objective The primary focus of this in vitro study was to investigate the osteogenic and immunomodulatory potential of WE43, a promising magnesium alloy tailored for clinical applications, and to test its osteogenic effect when a plasma electrolytic oxidation (PEO) surface modification is added. Results The present data revealed that WE43 implants show excellent biocompatibility and bioactivity, promoting the viability of osteoblasts and enhancing the expression of osteogenic genes, specially Alpl and Tnfrsf11b. PEO surface modification did not further enhance osteogenic differentiation. Notably, WE43 implants elicited a minimal inflammatory response in RAW264.7 murine macrophages, indicating good biocompatibility. Furthermore, supernatant collected from RAW264.7 murine macrophages cultured with WE43 implants stimulated the Alpl expression in MC3T3-E1 murine osteoblasts, demonstrating their potential osteoimmune effect. Conclusion The present findings highlight the promising potential of WE43 alloy as a biocompatible and osteoinductive biomaterial for bone regeneration applications. Their osteoimmune modulation further demonstrates the advantages of using this alloy system. Specifically, a minimal, well-controlled inflammatory response can promote a faster transition to the bone remodeling phase, leading to quicker and more effective bone regeneration. Methodology A comprehensive in vitro investigation was conducted to assess the impact of both WE43 and WE43 PEO on the viability, Alkaline Phosphatase (ALP) expression, osteogenic gene expression (Alpl, Tnfrsf11b, and Bglap), and mineralization of MC3T3-E1 murine osteoblasts. The osteoimmunomodulatory response to WE43 was evaluated using RAW264.7 murine macrophages by assessing their response to direct contact with the alloy.